Continuous control of radioactive emissions from proton LINAC - Skorkin, V.M.; Skorkin, A.V. (Вопросы атомной науки и техники, 2013)
On line control of atmospheric radioactive emissions is carried out by measuring the gamma-activity of radioactive gases in the special ventilation system of the proton linac with use scintillation gamma-ray detector. The distributed network detectors placed in INR territory allows carry out on line control of radiation situation near to Troitsk urban area. This monitoring system consists of the central server и gamma DKS-AT1121 dosimeters.